STUDENTS’ PERSPECTIVE ON MOTIVATING EFL ONLINE LEARNING PRACTICES - Erna Iftanti; Joko Tri Prastiyo; Rany Raissa Palupi (Indonesian EFL Journal, 2022)
Research has so far focused on challenges and problems encountered by either students or teachers about online learning. Meanwhile, research on finding out their positive and inspiring EFL online teaching and learning is not much given attention yet. Thus, to contribute to the previous related studies, this study is aimed at finding out the motivating EFL online learning practices from the students’ view. The data of this research were collected from conducting online survey through a google link to 174 students of English Department, UIN Sayyid Ali Rahmatullah, Tulungagung, Indonesia who have experienced the shift platform of learning from offline to online. They were then interviewed at random. The results of this study reveal that the motivating EFL learning practices can be interchangiably carried out synchronously through their most favorable online application and asynchronously. Teacher-related factors and learning materials are also perceived to be the important elements to create motivating online teaching practices. These research results are pedagogically implemented to build an effective EFL online teaching and learning.Keywords: students’ perspective; motivating online learning; motivating online teaching.